2017
DOI: 10.1155/2017/2910310
|View full text |Cite
|
Sign up to set email alerts
|

Malware Propagation and Prevention Model for Time-Varying Community Networks within Software Defined Networks

Abstract: As the adoption of Software Defined Networks (SDNs) grows, the security of SDN still has several unaddressed limitations. A key network security research area is in the study of malware propagation across the SDN-enabled networks. To analyze the spreading processes of network malware (e.g., viruses) in SDN, we propose a dynamic model with a time-varying community network, inspired by research models on the spread of epidemics in complex networks across communities. We assume subnets of the network as communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…The decomposed Markov processes deduced a widely approved result that a virus dies out quickly if / < 1/ 1 (A), where A is the adjacency matrix of the network, and 1 (A) is the largest eigenvalue of A. The network can also be dynamic, where nodes can transfer among communities [21]. The simulation results on two communities revealed that the node mobility can accelerate the malware propagation and improve the epidemic threshold.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The decomposed Markov processes deduced a widely approved result that a virus dies out quickly if / < 1/ 1 (A), where A is the adjacency matrix of the network, and 1 (A) is the largest eigenvalue of A. The network can also be dynamic, where nodes can transfer among communities [21]. The simulation results on two communities revealed that the node mobility can accelerate the malware propagation and improve the epidemic threshold.…”
Section: Related Workmentioning
confidence: 99%
“…where J 11 is an 2 × 2 diagonal matrix whose diagonal entries are − . We note that J 21 and J 31 are zero matrices. As a result, J is an upper block triangular matrix, and…”
Section: Group-based Mean-field Sis Modelmentioning
confidence: 99%
“…Where they proposed a coloring algorithm to limit the ability of a malicious controller to compromise its neighboring controllers. Lui et al [40] presented a SIS dynamic model with a time-varying community network to analyse the spreading processes of malware in SDN. However, these models did not consider the fact that the controllers can also infect the forwarding devices as we do in our models.…”
Section: Related Workmentioning
confidence: 99%
“…The output of our method is a Malicious Tenant List. A response module can manage and quarantine malicious tenants in the entire network by changing the flow table strategy . Figure depicts the steps and Figure illustrates the components of the proposed approach.…”
Section: Proposed Educational Approachmentioning
confidence: 99%